Structural approaches to targeting RNA terminal uridylytransferases - Yi, G (2023)
Let-7 microRNA (miRNA) plays a crucial role in the control of cell differentiation and proliferation, which also makes it a suppressor for the occurrence and development of tumors. Pre-let-7 is one of the intermediates in the maturation process of let-7 and two uridylyltransferases - ZCCHC6/TUT7, and ZCCHC11/TUT4 - play essential roles in the downstream processing of let-7 pre-miRNA. In the absence of RNA binding protein Lin28A, they perform 3’ mono-uridylation, leading to pre-let-7 maturation. In the presence of Lin28A, they together form a TUT4(7)-Lin28A-pre-let-7 holo-complex and perform oligo-uridylation, which subsequently leads to exonucleolytic pre-let-7 degradation. However, with no full structural information about TUT4/7, especially the lack of a complex structure with pre-let-7, their detailed uridylation mechanism is still a mystery.